The impact of gadget technology on students' interest in reading - Tarigan, Thomas Brenhard (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
Nowadays, technology is becoming increasingly sophisticated. One proof of the development of increasingly sophisticated technology is the existence of gadgets. Where gadgets are a form of technology that penetrates all circles including junior high school students who make children tend to prefer to be alone to use their Gadgets, rather than interacting with their peers. They spend more time just playing gadgets, so they don't have time to read books, be it textbooks or other books. So the importance of awareness of reading interest must also be further emphasised to students. And the purpose of this research is that the author focuses more on the discussion of the impact of Gadgets on students' interest in reading, especially students in class VII-1 SMP Negeri 8 Binjai.